2005
DOI: 10.1016/j.neuron.2005.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Increased Noise Level of Purkinje Cell Activities Minimizes Impact of Their Modulation during Sensorimotor Control

Abstract: While firing rate is well established as a relevant parameter for encoding information exchanged between neurons, the significance of other parameters is more conjectural. Here, we show that regularity of neuronal spike activities affects sensorimotor processing in tottering mutants, which suffer from a mutation in P/Q-type voltage-gated calcium channels. While the modulation amplitude of the simple spike firing rate of their floccular Purkinje cells during optokinetic stimulation is indistinguishable from tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(169 citation statements)
references
References 65 publications
11
157
1
Order By: Relevance
“…Previous studies have provided evidence that irregular Purkinje cell firing patterns contribute to cerebellar ataxia in Cacna1a mutants characterized by decreased Ca V 2.1-mediated Ca 2ϩ influx (Hoebeek et al, 2005;Walter et al, 2006), but did not unravel why a Cacna1a mouse mutant with an increased Ca V 2.1-mediated Ca 2ϩ influx is also ataxic. Here we reveal that the S218L mutation, which shifts the voltage dependence of Ca V 2.1-channel activation to more hyperpolarized values, renders Purkinje cells hyperexcitable and evokes irregular and slower Purkinje cell firing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have provided evidence that irregular Purkinje cell firing patterns contribute to cerebellar ataxia in Cacna1a mutants characterized by decreased Ca V 2.1-mediated Ca 2ϩ influx (Hoebeek et al, 2005;Walter et al, 2006), but did not unravel why a Cacna1a mouse mutant with an increased Ca V 2.1-mediated Ca 2ϩ influx is also ataxic. Here we reveal that the S218L mutation, which shifts the voltage dependence of Ca V 2.1-channel activation to more hyperpolarized values, renders Purkinje cells hyperexcitable and evokes irregular and slower Purkinje cell firing.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of ataxic mouse models, such as tottering and leaner mice (Fletcher et al, 1996;Mori et al, 2000) that carry mutations in the orthologous mouse Cacna1a gene revealed that a decreased Ca V 2.1-mediated Ca 2ϩ influx consistently results in disrupted Purkinje cell firing activity (Hoebeek et al, 2005;Walter et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Purkinje cells form the sole output cells of the cerebellar cortex and are capable of modifying their intrinsic frequency and regularity of firing (30)(31)(32). As such, the spiking pattern of the Purkinje cell is likely to encode information that is processed in the cerebellum, including during compensatory eye movements (26,27,33,34). We therefore recorded the spontaneous spiking activity of Purkinje cells in awake AS mice and in their WT littermates (Figure 3C).…”
Section: Tonic Inhibition Of Granule Cells Is Reduced In As Mice As mentioning
confidence: 99%
“…The eye movements were recorded at 240 Hz using a CCD camera fixed to the table, and pupil position was obtained using an eye-tracking system (ISCAN). Video calibrations and subsequent eye movement computations were performed with custom-made MATLAB (MathWorks) routines, as described previously (33). To analyze compensatory eye movements, phase and gain were calculated by fitting a sine function to the averaged eye and stimulus velocity traces.…”
Section: Ube3amentioning
confidence: 99%
“…Ataxia in EA2 is thought to be primarily due to Purkinje cell dysfunction either in neurotransmission 16 -18 or the precision of pacemaking. 19,20 By inhibiting the potassium currents, aminopyridines increase the duration of the action potential, thereby improving axonal conduction of action potentials and in particular the release of neurotransmitters. 21 Thus, 4AP and 3,4-diaminopyridine have been used for the symptomatic treatment of Lambert-Eaton myasthenic syndrome, 14,15 chronic spinal cord injury, 22 and multiple sclerosis (MS).…”
Section: Resultsmentioning
confidence: 99%